Geomatic based Urban Sprawl Detection of Salem City, India - R. Baskaran, S. Tamilenthi and (Recent Research in Science and Technology, 2011)
Urban sprawl refers to the extent of urbanisation, which is a global phenomenon mainly driven by population growth and large scale migration. In developing countries like India, where the population is over one billion, one-sixth of the worldÃ¢â‚¬â„¢s population, urban sprawl is taking its toll on the natural resources at an alarming pace. Urban planners require information related to the rate of growth, pattern and extent of sprawl to provide basic amenities such as water, sanitation, electricity, etc. In the absence of such information, most of the sprawl areas lack basic infrastructure facilities. Pattern and extent of sprawl could be dectected with the help ofÃ‚Â statelite imagesÃ‚Â and temporal data. ThisÃ‚Â is used to analysing the growth, pattern and extent of sprawl. This paper brings out the extent of sprawl taking place over a period of nearly four decades using GIS and Remote Sensing.